Optimisation of yield, flavonoids, and antioxidant activity via ultrasound-assisted extraction of bamboo leaves from Dinochloa sublaevigata S. Dransf. (Wadan) in Sabah, Malaysia - Muhammad Zahirul Amin Zulkifli; Mohammad Amil Zulhilmi Benjamin; Muhammad Daniel Eazzat Mohd Rosdan; Aniza Saini; Nor Azizun Rusdi; Mohd Azrie Awang (Elsevier B.V., 2025)
Dinochloa sublaevigata S. Dransf., an endemic bamboo species in Sabah, Malaysia, is valued for its ethnobotanical applications. However, research on extraction methods for its bioactive compounds and their bioactivities remains limited. This study optimised the D. sublaevigata leaf extract (DSLE) using response surface methodology (RSM) and ultrasound-assisted extraction (UAE). Extraction parameters, including ethanol concentration, temperature, ultrasonic amplitude, solid-to-solvent ratio, and extraction time, were initially screened using one-factor-at-a-time (OFAT) analysis to evaluate crude extract yield (CEY), total flavonoid content (TFC), and antioxidant capacity through 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging activity. Optimisation through a central composite design under RSM focused on temperature, amplitude, and solid-to-solvent ratio, while ethanol concentration (70 %) and extraction time (20 min) were fixed. The optimised conditions for DSLE—temperature (47.65 °C), amplitude (35.18 %), and solid-to-solvent ratio (1:25.11 g/mL)—achieved a CEY of 9.07 ± 0.13 %, TFC of 14.75 ± 0.03 mg RE/g extract, and DPPH of 91.78 ± 0.00 %. These results highlight a sustainable and efficient UAE method, establishing D. sublaevigata as a promising source for pharmaceutical and nutraceutical applications.